Effect of nano-clay addition and heat-treatment on tensile and stress-controlled low-cycle fatigue behaviors of aluminum-silicon alloy: Effect of nano-clay addition and heat-treatment (Fracture and Structural Integrity, 2021)
The objective of the present paper is to investigate the stress-controlled low-cycle fatigue behavior of piston aluminum-silicon (AlSi) alloy reinforced with nano-clay particles and T6 heat-treatment. The piston aluminum-silicon alloy strengthened by 1 wt.% nano-clay particles were prepared by the stir casting method and then subjected to the heat-treatment. The optical microscopy analysis demonstrates that heat-treatment changed the size, morphology, and distribution of silicon phases through the microstructure of the aluminum matrix. In addition to tensile tests, stress-controlled low-cycle fatigue experiments at different loading conditions including the variation of the mean stress, the stress rate, and the stress amplitude were conducted at room temperature. The obtained experimental results showed no clear improvement in either mechanical or fatigue properties of the material. Moreover, the density measurements using the Archimedes method reveal a higher content of the porosity in nano-composite. It was observed that the reinforcement (nano-particles and heat-treatment) can change the cyclic behavior of the AlSi alloy, significantly. The cyclic hardening feature of the AlSi alloy changed to cyclic softening and also the fatigue lifetime and the ratcheting resistance decreased after the nano-particles addition and heat-treatment. Through the microstructural analysis, it was indicated that the neglecting of higher kinematics of age hardening in nano-composite was the major source of mechanical properties reduction. In the end, it was shown that the fatigue lifetime of samples can be described adequately utilizing a modified plastic strain energy technique considering the mean stress effect.
Keywords: Aluminum-silicon alloys; Stress-controlled cyclic behavior; Fatigue lifetime; Nano-clay-particles; Heat-treatment